Employee Voice Behavior in Regional Banking: The Effects of Job Autonomy, Person–Organization Fit, and Work Engagement - Akbar Mursalin; Elfitra Azliyanti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
In the era of industrial and digital transformation, organizations are required to remain adaptive and innovative to maintain competitiveness. The banking sector, including regional institutions such as Bank Nagari, faces increasing customer demands and service-related complaints, necessitating stronger employee involvement in continuous improvement efforts. This study examines the influence of job autonomy, person–organization fit, and work engagement on employee voice behavior at the Main Branch Office (KCU) of Bank Nagari, located on Jalan Pemuda No. 21, Padang. The research was conducted in 2025 using a quantitative, cross-sectional design. Data were collected from 108 employees through structured questionnaires and analyzed using multiple linear regression. The results indicate that person–organization fit has a significant positive effect on employee voice behavior (Coef = 0.21; p = 0.000), whereas job autonomy (Coef = 0.06; p = 0.455) and work engagement (Coef = –0.007; p = 0.879) show no significant influence. These findings suggest that value alignment between individuals and the organization is more essential in fostering employee voice than structural or motivational aspects. Practically, the study highlights the importance of creating an open organizational climate, strengthening recruitment based on value congruence, internalizing organizational culture, and promoting leadership that encourages employee expression to enhance innovation and organizational development within the banking sector.